European economic security and access to critical raw materials: Trade, diversification, and the role of Mercosur - Oscar Guinea; Vanika Sharma (European Centre for International Political Economy (ECIPE), 2023)
Access to secure and stable supply of critical raw materials (CRMs) is vital for Europe's economic security. These raw materials, which are indispensable inputs for Europe's modernisation, are supplied by a handful of countries. Among them, China and Russia are two of the most important European suppliers of CRMs. This dependency leaves the EU exposed to Chinese and Russian policies that may harm Europe's economic and political interests.
Keywords: 330